PENGARUH PENGALAMAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN PADA INDUSTRI KAPAL INDONESIA (PERSERO) - Yusran, Yusran; Rusli, Muh (Patria Artha University, 2022)
This study found the results that all hypotheses in the study have been proven. 1) Work experience has a positive and significant effect on employee performance, 2) Work facilities have a positive and significant effect on employee performance, and 3) Work experience and work facilities together have a positive and significant effect on employee performance. The implication of this research is that work experience and work facilities have an equally important role both individually and collectively in improving employee performance.